2022
DOI: 10.1007/s11914-022-00722-1
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Demineralization, Part I: Attrition, Erosion, Abfraction, and Noncarious Cervical Lesions

Abstract: Purpose of the Review Compare pathophysiology for infectious and noninfectious demineralization disease relative to mineral maintenance, physiologic fluoride levels, and mechanical degradation. Recent Findings Environmental acidity, biomechanics, and intercrystalline percolation of endemic fluoride regulate resistance to demineralization relative to osteopenia, noncarious cervical lesions, and dental caries. Summary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 163 publications
0
25
0
1
Order By: Relevance
“…Tooth flexure (deformation) of a mandibular first premolar using FEA revealed that occlusal loads of 200 N are 10‐fold greater for nonaxial loading compared to axial loads 72 . Also, the deepest aspect of a wedge lesion is the stress riser so it is the most susceptible to the progressive fatigue failure that advances the lesion 73 when the tooth is flexed 3 . These data suggest the mineralized tissue at the base of a NCCL is failing under surface compression 3 .…”
Section: Etiologymentioning
confidence: 99%
See 3 more Smart Citations
“…Tooth flexure (deformation) of a mandibular first premolar using FEA revealed that occlusal loads of 200 N are 10‐fold greater for nonaxial loading compared to axial loads 72 . Also, the deepest aspect of a wedge lesion is the stress riser so it is the most susceptible to the progressive fatigue failure that advances the lesion 73 when the tooth is flexed 3 . These data suggest the mineralized tissue at the base of a NCCL is failing under surface compression 3 .…”
Section: Etiologymentioning
confidence: 99%
“…Natural fruit tannins (tannic acid) are prevalent in higher quality wine which may have a pH of 3.5 or less. The European culture of wine and cheese consumed together is a wise social strategy since the cheese buffers the acidity of the wine, tends to adhere to enamel surfaces, and supplies both calcium and phosphate ions for remineralization 3 …”
Section: Etiologymentioning
confidence: 99%
See 2 more Smart Citations
“…12 | num. 4 | in the medical literature [5][6][7][10][11][12]. Restoration of tooth tissues with such defects presents certain difficulties, as a special approach to dissection, treatment, and the right choice of filling material is required.…”
Section: Introductionmentioning
confidence: 99%